Amyloid beta oligomers-induced parkin aggravates ER stress-mediated cell death through a positive feedback loop. (May 2022) - Kam, Min Kyoung; Kim, Bokyung; Lee, Dong Gil; Lee, Hong Jun; Park, Young-Ho; Lee, Dong-Seok
Abstract: Recently, Parkin has been reported to induce endoplasmic reticulum (ER) stress. In addition, amyloid beta oligomers (AβO), hallmarks of Alzheimer's disease (AD), also increase ER stress in neurons. Because a mutation in the Parkin gene is a well-known predominant cause of familial Parkinson's disease (PD), Parkin has been well studied in PD but has not been well researched in AD. In this study, we investigated the role of AβO-mediated Parkin associated with ER stress in AD. For AD-based research, we used AβO treatments in mouse hippocampus-derived HT-22 cells. We stably expressed Parkin in HT-22 cells to confirm the hypothesis and used siParkin for downregulation of Parkin expression. Moreover, using hippocampi from amyloid precursor protein/presenilin 1/Tau triple transgenic mice (3xTg‐AD mice), which are used for AD models, we confirmed the relationship between ER stress and Parkin in vivo. We observed that ATF4 upregulated AβO-increases in Parkin. Parkin overexpression aggravated ER stress in AβO-treated HT-22 cells and the hippocampi of 3xTg‐AD mice. Parkin downregulation led to no significant change when compared to AβO-treated cells. Moreover, Parkin-mediated ER stress was not related to oxidative stress. Our study indicates that AβO-induced ATF4 upregulated Parkin levels and that Parkin increases ER stress as a positive feedback loop. Through this study, our findings provide a foundation for future studies on the specific mechanisms related to the role of Parkin in AD. Highlights: In HT-22, AβO-mediated ER-stress increased Parkin expression. AβO-mediated Parkin upregulated ER-stress as positive feedback. AβO-mediated Parkin level was not related with oxidative stress.